Denying and establishing paternity de lege lata according to the Romanian private international law vs. de lege ferenda according to the Council Regulation in matters of parenthood and on the creation of a European Certificate of Parenthood - Aniţei, Nadia-Cerasela; Dornean Păunescu, Raluca Laura (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The study presents an analysis of the procedure for denying paternity and establishing paternity, as they are currently carried out in Romania according to Romanian private international law, respectively in antithesis, the procedures for establishing filiation de lege ferenda according to the Proposal for a regulation of the council on jurisdiction, the applicable law, the recognition of court decisions and the acceptance of authentic documents in matters of filiation and on the creation of a European certificate of filiation.Ab initio, preliminary clarifications are presented regarding the provisions of Romanian private international law with reference to filiation, the filiation of the child of the marriage in Romanian private international law, the law applicable to the child born in wedlock, the way of interpreting the provisions of the Romanian Civil Code regarding the determination of the law applicable to the filiation of the child born in wedlock, the scope of the filiation law, the law applicable to the legitimization of a child born before marriage, respectively proposals de lege ferenda.Next, the paper addresses references regarding the filiation of the child out of wedlock in the Romanian private international law, respectively the legal seat of the provisions regarding the filiation of the child out of wedlock in the Romanian private international law, the law applicable to the filiation of the child out of wedlock, the field of the law applicable to the filiation to the child out of wedlock, as well as the law applicable to filiation as a result of human reproduction with a third donor, respectively the law applicable to filiation as a result of human reproduction with a third donor in the case of a child born in wedlock, as well as the law applicable to filiation as a result of human reproduction with a third donor in the case of a child out of wedlock.The authors then present due clarifications regarding the dichotomy of the provisions of Romanian private international law and the correspondence with the Council’s proposed regulation on filiation, noting the jurisdiction, the applicable law, and the recognition.In the corollary, a case study is highlighted, a case-law element, which denotes the case-law in Romania, respectively the hypothesis of de lege ferenda solution of the situation, by virtue of the proposal for the Regulation in matters of parenthood.
Keywords: filiation in Romanian private international law; denial of paternity; establishment of paternity; proposal of the Regulation in matters of parenthood; dichotomy